Occurrence and distribution of Panstrongylus megistus (Burmeister, 1835) (Hemiptera, Reduviidae) in a metropolitan area of Southern Brazil - Mello, Fernanda de; Souza, Getúlio Dornelles; Bedin, Cleonara; Duarte, Marcelo Bergamin; Leon, Ítalo Ferreira de; Villela, Marcos Marreiro (Revista do Instituto de Medicina Tropical de São Paulo, 2023)
Two triatomine genera (Panstrongylus and Triatoma) have essentially been recorded in Rio Grande do Sul State, Brazil. Panstrongylus megistus should be highlighted since this species is one of the main vectors of Trypanosoma cruzi in Brazil, due to its wide geographical distribution and the high susceptibility to this protozoan. This study aimed to present not only the occurrence and distribution of P. megistus in the Porto Alegre city’s metropolitan area (PAMA), Rio Grande do Sul State, Brazil, but also the rates of T. cruzi infection, from 2009 to 2020. The PAMA, which comprises 34 cities and 4.4 million habitants, extends across the transition area in two biomes – Pampa and Mata Atlantica – found in the state. Results showed that P. megistus was recorded in 76.5% of cities (i.e., 26 out of 34), mainly in Porto Alegre city, where the vector was found in 11 out of the 12 years that were monitored. Three hundred and nineteen specimens were captured. Two hundred and sixty-seven specimens (83.7%) were located intradomicile (p < 0.0001), while 52.3% positivity for T. cruzi was found. Thus, P. megistus is important in the PAMA, because it invades and colonizes the households. Moreover, the high rates of T. cruzi infection have drawn attention.